Characterization and differentiation of chemical fingerprints of virgin and used lubricating oils for identification of contamination or adulteration sources. (1st January 2016) - Yang, Chun; Yang, Zeyu; Zhang, Gong; Hollebone, Bruce; Landriault, Mike; Wang, Zhendi; Lambert, Patrick; Brown, Carl E.
Abstract: Lubricating oil plays a critical role to reduce friction and to ensure the machines are more energy efficient in terms of fuel consumption and power output. The use of unqualified lube oil can result in malfunctions and damage to engines and machinery. Since petroleum-based lube oils are among the most valuable refined products, in some regions, fake, used, or waste lube oils have occasionally been deliberately adulterated into lube oil to extend the volume sold. On the other hand, used or waste lube oil is hazardous material, containing contaminants such as metals and polycyclic aromatic hydrocarbons produced by the engine during use. It becomes an environmental problem when it is purposely disposed of or accidentally spilled into the environment. Some jurisdictions now have relevant regulations to prohibit these illegal activities; therefore, forensic analysis of lube oils is essential to differentiate fake and used lube products from virgin oils, to identify and to track the adulteration source, and to identify the source of spilled oil. This work involved a fingerprinting analysis of a suite of oil samples including a virgin lube oil, used motor oils, a waste lube oil from a motor workshop, a regular diesel oil and a biodiesel blend, etc. The chemical fingerprints such as the abundance and distribution profiles of total petroleum hydrocarbon, polycyclic aromatic hydrocarbons (PAHs), particularly the higher molecular pyrogenic PAHs, and biomarkers indicate that the used and the waste lube oils are mixtures of mainly lube oil and a small amount of diesel type fuel. The presence of C16 to C20 fatty acid methyl esters (FAME) with the dominance of C16:0 and C18:1 isomers suggests that the used and the waste lube oils both contain residual palm oil-based biodiesel.